Iron Metabolism and Haematological Changes in Sheep During The Periparturient Period - Deniz, Ömer; Bozacı, Serkan; Soytürk, Berrak Işık; Şimşek, Abdullah; Şafak, Tarık; Tümer, Kenan Çağrı (Dicle University, 2025)
This study sought to evaluate changes in plasma iron (Fe), unsaturated iron-binding capacity (UIBC), and hematocrit (Hct) levels in pregnant ewes before and after parturition. Blood samples were collected 10 days before and 10 days after birth, and concentrations of Fe, UIBC, and Hct were evaluated. The results indicated a substantial reduction in plasma iron levels postpartum (p=0.042) and a considerable elevation in UIBC levels (p=0.004). No statistically significant variation in Hct level was observed between the prepartum and postpartum periods (p=0.531). The reduction in plasma iron levels may be linked to heightened physiological requirements for iron and bleeding associated with parturition. Increased UIBC levels indicate changes in transferrin binding capacity during the postpartum period. Hct levels remained consistent postnatally, signifying the preservation of hematopoietic equilibrium.